Role of catecholaminergic neurones of the caudal ventrolateral medulla in cardiovascular responses induced by acute changes in circulating volume in rats - Pedrino, Gustavo Rodrigues; Maurino, Isabela; de Almeida Colombari, Debora Simoes; Cravo, Sergio Luiz (Blackwell Publishing, 2006)
Several findings suggest that catecholaminergic neurones in the caudal ventrolateral medulla (CVLM) contribute to body fluid homeostasis and cardiovascular regulation. The present study sought to determine the effects of lesions of these neurones on the cardiovascular responses induced by changes in circulating volume. All experiments were performed in male Wistar rats (320-360 g). Medullary catecholaminergic neurones were lesioned by microinjection of anti-dopamine beta-hydroxylase-saporin (6.3 ng in 60 nl; SAP rats, n = 14) into the CVLM, whereas sham rats received microinjections of free saporin (1.3 ng in 60 nl, n = 15). Two weeks later, rats were anaesthetized (urethane, 1.2 g kg(-1), I.V..), instrumented for measurement of mean arterial pressure (MAP), renal blood flow (RBF) and renal vascular conductance (RVC), and infused with hypertonic saline (HS; 3 M NaCl, 0.18 ml (100 g body weight)(-1), I.V.) or an isotonic solution (volume expansion, VE; 4% Ficoll, 1% of body weight, I.V.). In sham rats, HS induced sustained increases in RBF and RVC (155 +/- 7 and 145 +/- 6% of baseline, at 20 min after HS). In SAP rats, RBF responses to HS were blunted (125 +/- 6%) and RVC increases were abolished (108 +/- 5%) 20 min after HS. Isotonic solution increased RBF and RVC in sham rats (149 +/- 10 and 145 +/- 12% of baseline, respectively, at 20 min). These responses were reduced in SAP rats (131 +/- 6 and 126 +/- 5%, respectively, at 20 min). Pressor responses to HS were larger in SAP rats than in sham rats (17 +/- 5 versus 9 +/- 2 mmHg, at 20 min), whereas during VE these responses were similar in both groups (6 +/- 3 versus 4 +/- 6 mmHg, at 20 min). Immunohistochemical analysis indicates that microinjections of anti-D beta H-saporin produced extensive destruction within the A1/C1 cell groups in the CVLM. These results suggest that catecholaminergic neurones mediate the cardiovascular responses to VE or increases in plasma sodium levels.